2019
DOI: 10.14715/cmb/2019.65.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Different VDR, VDBP genotypes and vitamin D levels may effect obstructive sleep apnea syndrome

Abstract: Obstructive sleep apnea syndrome (OSAS) is a highly prevalent disorder which results in markedly reduced (hypopnea) or absent (apnea) airflow at the nose/mouth. Since vitamin D deficiency has found in an association with some disorders it is thought to be related with OSAS progression. The aim of this study is to investigate the association between VDR, VDBP mutations, vitamin D level and some environmental risk factors with OSAS. Fifty individuals who were diagnosed as OSAS were selected as patients, 50 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Only two small studies have investigated the role of VDR polymorphisms in other sleep disorders. In the first study, Kirac et al 53 investigated two VDR gene polymorphisms (FokI and BsmI) in 50 individuals with obstructive sleep apnea (OSA) and 50 healthy individuals. They showed that VDR polymorphisms were significantly associated with OSA 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two small studies have investigated the role of VDR polymorphisms in other sleep disorders. In the first study, Kirac et al 53 investigated two VDR gene polymorphisms (FokI and BsmI) in 50 individuals with obstructive sleep apnea (OSA) and 50 healthy individuals. They showed that VDR polymorphisms were significantly associated with OSA 53 .…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, Kirac et al 53 investigated two VDR gene polymorphisms (FokI and BsmI) in 50 individuals with obstructive sleep apnea (OSA) and 50 healthy individuals. They showed that VDR polymorphisms were significantly associated with OSA 53 . A second study conducted by Abbas et al (2019) recruited 240 Egyptian adults with OSA and 120 matched controls and found a gradient dose–response, as one mutated allele (Ff) increased the risk of OSA by more than two times (OR: 2.66, p = 0.03), and when both mutated alleles were present (ff) the risk of OSA was 10 times higher (OR: 10.59, p < 0.001) 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D pathway genes, such as VDR, CYP27A1, CYP27B1, CYP2R1, CYP24A1 , and vitamin D binding protein ( VDBP ) not only control vitamin D biosynthesis and its transport but also influence the cytokine levels in various autoimmune diseases, including T1D ( 54 , 55 , 56 ). Vitamin D plays a major role in the regulation of insulin secretion from pancreatic β-cells ( 57 , 58 ). VDR polymorphisms in the 3´UTR region are well known to affect its translation and mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the VDR FokI polymorphism is associated with excessive daytime sleepiness. Kirac et al [ 33 ] investigated VDR FokI (rs2228570) and B sm I (rs1544410) and vitamin D-binding protein rs4588 and rs7041 mutations in OSAS patients. They reported that CA genotype in rs4588, CC genotype in rs2228570, and AA genotype in rs1544410 mutations were statistically significant in patients.…”
Section: Discussionmentioning
confidence: 99%